2015
DOI: 10.1055/s-0035-1551836
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Zirconium Bearing Surfaces in Total Knee Arthroplasty: Lessons Learned

Abstract: Polyethylene wear in total knee arthroplasty is a still unsolved problem resulting in osteolysis and long-term failure of knee joint replacement. To address the problem of polyethylene wear, research aimed for an optimal implant design and for an optimal combination of bearing surfaces. Oxidized zirconium was introduced to minimize surface wear and thus potentially increase long-term implant survival. This review comprises the current literature related to in vitro and in vivo studies evaluating performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Kim et al [19] reported that the PE wear particles from CoCr TKRs were not different in weight, size or shape than those from OxZr TKRs which would be expected if the femoral components of both materials roughened to the same extent after a period of time in vivo. The results in this study and in Kim et al [19] support the findings that report no clinical difference between TKRs with OxZr femoral components and TKRs with CoCr femoral components at the 10 year follow up period [12,17,18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Kim et al [19] reported that the PE wear particles from CoCr TKRs were not different in weight, size or shape than those from OxZr TKRs which would be expected if the femoral components of both materials roughened to the same extent after a period of time in vivo. The results in this study and in Kim et al [19] support the findings that report no clinical difference between TKRs with OxZr femoral components and TKRs with CoCr femoral components at the 10 year follow up period [12,17,18].…”
Section: Discussionsupporting
confidence: 90%
“…In 2004, Oxidised Zirconium (OxZr) (a surface-modified metal comprising a uniform ceramic surface with a gradual transition from ceramic oxide to substrate metal alloy) was introduced for TKR femoral components in an attempt to reduce PE wear associated failures [11,12]. With a greater surface hardness and wettability than cobalt-chromium alloy (CoCr) [13], OxZr femoral components should theoretically lead to the reduction of PE wear.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative bearing surfaces to Cobalt Chrome (Co-Cr), such as Oxidized Zirconium (Oxinium; Smith and Nephew, Memphis, TN, USA) have been introduced(6)(7) (8) in an attempt to reduce polyethylene wear and hence reduce long-term TKA failure rates. While non-comparative reports have been described as promising(9) (10) (11)(12)(13)(14) (15), no short or long term clinical studies exist showing the superiority of Oxinium on a polyethylene bearing surface.…”
Section: Introductionmentioning
confidence: 99%
“…Developments in the production and processing of polyethylene inserts have decreased wear rates 67 . However, development of sequentially irradiated or annealed polyethylene and vitamin E polyethylene were shown to retain mechanical properties of highly cross-linked polyethylene with lower wear rates and fewer free radicals 68 , but problems with strength and fatigue resistance remain. Oxidized zirconium knee arthroplasties have been proposed to provide durability of metal component, reducing the coefficient of friction of the ceramic surface.…”
Section: Total Knee Replacement: New Evidencementioning
confidence: 99%
“…Oxidized zirconium knee arthroplasties have been proposed to provide durability of metal component, reducing the coefficient of friction of the ceramic surface. This type of material has been associated with decreased wear rates 68,69 .…”
Section: Total Knee Replacement: New Evidencementioning
confidence: 99%